RESEPSI PERNIKAHAN (Antara Sakralitas Agama, Hukum, dan Tuntutan Adat) - Muttaqin, Muhammad Ngizzul (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
Celebrating a wedding reception is a necessity and happiness for the bride and groom and their families. In addition to being governed by religion and the state law, wedding receptions are also carried out on the basis of the customs and habits of the people. But in today’s society’s understanding of wedding receptions as a necessity and a requirement that must be carried out based on the luxury and model of events that are mostly carried out by the environment. Until in the end many forget the substance of marriage and favor tradition. As a literature-based study and literature review, this paper will highlight the implementation of a wedding reception from the viewpoint of religion, law and customary demands. The results of this paper are expected to contribute thoughts and understanding of the substance of the wedding reception.